Research on the Characteristic of Rubber Belt Type CVT in Baja Racing Car - Zhaohui Jin; Yuan Shan; Da Wang; Qingsong Sun; Zhenyu Ma; Mingyi Li (Jixie chuandong)
In order to improve the transmission efficiency of the rubber CVT and better match the power performance of the engine and the whole vehicle，the bench test of the engine and CVT is carried out，and the curves of starting motor，external characteristics of CVT and influencing factors of CVT are drawn. The results show that，without changing the structure of the CVT，the temperature is the main factor that influence the efficiency of the CVT，and at the age of 55 ℃ CVT maintain a high efficiency. According to the driving force curve drawing CVT external characteristic curve，determine the total transmission ratio for the gear reducer is 12.9，and determine the CVT light left block and the combination of the heavy spring can make the car can quickly reach the highest speed.